Echocardiographic assessment of a cardiac lymphoma: beyond two-dimensional imaging - Gaspar, A (2012)
Lymphoma is usually recognized as the third most frequent metastatic malignancy involving the heart. In recent years, the incidence of cardiac lymphoma has increased, mainly because of HIV-infected patients. We present a case of secondary cardiac lymphoma in an HIV patient presenting with heart failure. Transthoracic echocardiography showed increased left ventricular (LV) wall thickness and an extensive mass in the right cavities with involvement of the tricuspid annulus (Figure 1). Doppler tissue imaging (DTI) showed reduced systolic and diastolic velocities at mitral and tricuspid annulus, compatible with systolic and diastolic myocardial dysfunction, likely owing to infiltration. After 2 weeks of chemotherapy, repeated exam showed significant reduction of the tumour mass and of the LV wall thickness, as well as normalized systolic and diastolic velocities at mitral and tricuspid annulus, as assessed by DTI. Use of transthoracic echocardiography, mostly two-dimensional imaging, has been described for several years for the diagnosis of cardiac involvement as well as for the assessment of tumour regression in response to chemotherapy. The present case report highlights the potential utility of other echocardiographic modalities, particularly DTI, for the assessment of cardiac lymphoma but also for monitoring the tumour response to adequate therapy.